Prevalence, common causes and effects of technical debt: Results from a family of surveys with the IT industry - Ramač, Robert (2022)
Context: The technical debt (TD) metaphor describes actions made during various stages of software development that lead to a more costly future regarding system maintenance and evolution. According to recent studies, on average 25% of development effort is spent, i.e. wasted, on TD caused issues in software development organizations. However, further research is needed to investigate the relations between various software development activities and TD. Objective: The objective of this study is twofold. First, to get empirical insight on the understanding and the use of the TD concept in the IT industry. Second, to contribute towards precise conceptualization of the TD concept through analysis of causes and effects. Method: In order to address the research objective a family of surveys was designed as a part of an international initiative that congregates researchers from 12 countries—InsighTD. At country level, national teams ran survey replications with industry practitioners from the respective countries. Results: In total 653 valid responses were collected from 6 countries. Regarding the prevalence of the TD concept 22% of practitioners have only theoretical knowledge about it, and 47% have some practical experiences with TD identification or management. Further analysis indicated that senior practitioners who work in larger organizations, larger teams, and on larger systems are more likely to be experienced with TD management. Time pressure or deadlinewas the single most cited cause of TD. Regarding the effects of TD: delivery delay, low maintainability, and rework were the most cited. Conclusion: InsighTD is the first family of surveys on technical debt in software engineering. It provided a methodological framework that allowed multiple replication teams to conduct research activities and to contribute to a single dataset. Future work will focus on more specific aspects of TD management.